(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Arteriovenous malformation (AVM) of the brain is a congenital vascular anomaly characterized by abnormal connections between arteries and veins, often leading to hemorrhage, seizures, or neurological deficits. Recent studies have focused on genetic predispositions that may influence the development and clinical manifestations of AVM. Among these, the matrix metalloproteinase 3 (MMP3) gene plays a key role in extracellular matrix remodeling and vascular wall integrity. The rs522616 polymorphism of the MMP3 gene, representing a single A/G nucleotide substitution, has been hypothesized to influence enzyme activity and, consequently, AVM pathogenesis. This study investigated the distribution of allelic and genotypic variants of rs522616 in 95 patients with AVM and 60 control individuals of Uzbek nationality. Genotyping revealed no statistically significant differences in allele (A vs. G) or genotype (A/A, A/G, G/G) frequencies between the AVM and control groups, indicating that the polymorphism is not a direct determinant of AVM susceptibility. However, subgroup analyses demonstrated a higher prevalence of the unfavorable G allele and particularly the homozygous G/G genotype among patients with hemorrhagic AVM, suggesting a potential genetic predisposition to severe clinical outcomes. Although statistical significance was not reached, the observed trend highlights the possible contribution of rs522616 polymorphism to AVM progression and complications. These findings suggest that rs522616 polymorphism of the MMP3 gene may serve as a candidate genetic marker for predicting hemorrhagic risk in AVM patients. Further large-scale, multi-ethnic studies are necessary to validate the observed associations and to better understand the role of MMP3 polymorphisms in cerebrovascular pathologies. Ultimately, genetic profiling may contribute to the development of personalized approaches for prognosis and management of AVM complications.